The BLOOD PRESSURE DIFFERENCES AFTER GIVEN TOUCH THERAPY BY CONTROLLING IMT - indra yulianti; Rina Mardiyana; Ifa Roifah (INTERNATIONAL JOURNAL OF NURSING AND MIDWIFERY SCIENCE (IJNMS), 2020)
Hypertension often results in dangerous conditions that are often not realized and often do not cause complaints. Hypertension is also often referred to as the silent kiler because it is a deadly disease. Even hypertension can lead to other deadly diseases and can increase the risk of heart attack, stroke and kidney failure. The research design used Quasi Experiment with Non Equivalent Control Group design with pre-postest control one group design. The research was conducted in the working area of ​​the Dlanggu Health Center on September 2020. The population in this study were all hypertension sufferers. The sampling technique used simple random sampling of 60 people. The instrument used was a sphygmomanometer, measuring height and weight and an observation sheet. Data analysis used the Ancova test with the assumption of normal and homogeneous data distribution. Ancova analysis results showed that BMI did not affect systolic blood pressure (F = 0.014, p value 0.907> α), but there was a difference in systolic blood pressure between the control group and the treatment group (F = 105.06, p-value 0,000 <α). The results of the ancova analysis showed that BMI did not affect diastolic blood pressure (F = 0.003, p value 0.953> α), but there was a difference in diastolic blood pressure between the control group and the treatment group (F = 80.899, p-value 0.000 <α). It can be concluded that the difference in systolic and diastolic blood pressure after being given Touch Therapy is not controlled by the BMI variable. This is because blood pressure is controlled by other influencing factors, including stress and physical activity.